Analysis of Innovative Learning and Student Learning Outcomes During the Covid-19 Pandemic - Rosma Nababan; Fransiskus Gultom; Alim Perangin-angin; Losten Tamba (Jurnal Penelitian Pendidikan IPA, 2023)
The purpose of this research is to describe the analysis of innovative learning and student learning outcomes in class X SMA Jambi Medan during the Covid-19 pandemic. This research is qualitative research, the research subjects were students in class X SMA Jambi Medan totaling 33 people. Data collection techniques were obtained through interviews and questionnaires. The results showed that the science learning process in class X SMA Jambi Medan during the Covid-19 pandemic was carried out offline using a shift system by applying the discovery learning learning model with a scientific approach and combined with several mind mapping learning methods, group discussions, question and answer and assignment. Student participation in science learning during the Covid-19 pandemic was good. Students participate actively in the science learning process. Assessment of students' science learning outcomes achieves the minimum completeness criteria.